2010
DOI: 10.1021/jp106330c
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Polymers and Single-Walled Boron Nitride Nanotubes: A Molecular Dynamics Simulation Approach

Abstract: In this work, we used a molecular dynamics (MD) simulation approach to investigate the interfacial binding of boron nitride nanotubes (BNNTs) with poly[m-phenylenevinylene-co-(2,5-dioctyloxy-p-phenylenevinylene)] (PmPV), polystyrene (PS), and polythiophene (PT). Quantum partial charges of BNNT-polymer composites were determined by density functional theory (DFT) calculations and then included in MD simulations. The interaction energy between nanotubes and polymer molecules was computed, and the morphology of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 54 publications
4
53
0
Order By: Relevance
“…17 Our experiments with MWCNTs show that rra-P3HT also debundles MWCNTs, and a weak broad band is observed (530−680 nm), indicating planarization and adsorption of rra-P3HT on the MWCNTs ( Figure S2). However, the absorption band has a more diffuse structure than that for BNNTs under similar conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 75%
“…17 Our experiments with MWCNTs show that rra-P3HT also debundles MWCNTs, and a weak broad band is observed (530−680 nm), indicating planarization and adsorption of rra-P3HT on the MWCNTs ( Figure S2). However, the absorption band has a more diffuse structure than that for BNNTs under similar conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 75%
“…18,20,21 Coleman and coworkers reported exfoliation of BNNSs in isopropanol (IPA), as well as MoS 2 and WS 2 in N-methyl-2-pyrrolidone (NMP). [24][25][26][27][28] In one prior study of particular interest, 25 attractive interactions between oligomers of three polymers and BNNT were studied by simulations in the absence of any solvent medium. 19 Our current study focuses on the use of polyvinylpyrrolidone (PVP) as a dispersant for a broad class of 2D layered nanosheets (BNNSs, MoS 2 , and WS 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…25 The use of atomistically detailed models allows us to explicitly account for the specific molecular interactions in the system. (1) We demonstrate dispersion of these nanosheets in not only water but also a wide range of organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…The projected interaction between TPU and h‐BN is depicted in Scheme . Previously it was shown that BN could interact with some polymers through π‐π interactions or other ways . For instance, it was reported that due to the interactions between BN and poly(methyl methacrylate), polystyrene, poly(vinyl butyral), or poly(ethylene vinyl alcohol), a dramatic reduction was observed in the coefficient of thermal expansion of these BN containing polymers .…”
Section: Resultsmentioning
confidence: 99%